Impact of Farmers Producer Company on Members - P.P.Wankhade; M.K.Rathod; B.N.Uikey; R.S.Waghmare; Mendhe, Harsha (Journal of Agricultural Extension Management, 2022)
Farmers Producer Companies (FPCs) are envisaged to collectivize small farmers for backward linkage for input like seed, fertilizers, credit, insurance, knowledge and extension services and forward linkage. The present study attempts to assess the extent of impact of Farmers Producer Company (FPC) on their members in relation to family income socioeconomic behavior, risk taking ability, marketing behavior, awareness about scientific fact and new technology. The Ganeshpur Farmers Producer Company, Mouza Jakha, Taluka & Dist. Bhandara in Maharashtra was selected to study impact of FPC on its members on broad parameters like change in annual income, change in annual expenditure, change in annual saving, change in social participation, and change in employment generation. It was found that there the FPC made an overall impact of 19.63 per cent on its members after they joined it.